Aerobic exercise and brain structure among military service members and Veterans with varying histories of mild traumatic brain injury: A LIMBIC-CENC exploratory investigation - Samuel R. Walton; John J. Fraser; Jessie R. Oldham; Mark L. Ettenhofer; Patrick Armistead-Jehle; Hannah M. Lindsey; Naomi J. Goodrich-Hunsaker; Emily L. Dennis; Elisabeth A. Wilde; Sarah M. Jurick; Michael J. Hall; Randel L. Swanson; et al. (PLoS ONE, 2025)
Objectives To explore associations of recent moderate-to-vigorous aerobic exercise (MVAE) participation and lifetime mild traumatic brain injury (mTBI) history with measures of brain gray matter volumes among military service members and Veterans (SMVs). Methods Participants (n = 1,340; aged 41.3 ± 10.3 years; 13% female) were SMV’s who participated in the Long-term Impact of Military-relevant Brain Injury Consortium-Chronic Effects of Neurotrauma Consortium Prospective Longitudinal Study (LIMBIC-CENC PLS). MVAE participation was self-reported via the Behavioral Risk Factor Surveillance System and categorized according to current MVAE recommendations (Inactive, Insufficiently Active, Active, and Highly Active). Lifetime mTBI history was queried via validated structured interview and categorized as 0 mTBI, 1-2 mTBIs, 3 + mTBIs. Structural MRI (T1- and T2-weighted images) were used to measure gray matter volumetrics: ventricle-to-brain ratio (VBR); bilateral volumes of the frontal, parietal, temporal, occipital, cingulate, hippocampus, amygdala, and thalamus regions. Multivariable linear regression models were fit to test associations of MVAE participation, mTBI history, and their interaction on each of the volumetric outcomes while controlling for age, sex, education attainment, and PTSD symptoms. Effects were considered statistically significant if the corresponding unstandardized beta (B) and 95% CI did not include 0. Results Regarding main effects, participants in the Inactive MVAE group had significantly larger VBR values (worse outcome) than those in the Insufficiently Active group (B[95%CI] = -0.137[-0.260, -0.014]). Interaction effects showed participants with no lifetime mTBIs in the Highly Active group had larger VBR values (worse outcome) when compared to those in the Inactive and Insufficiently Active groups. SMVs with 3 + lifetime mTBIs who were Highly Active also had smaller VBR values (better outcome) when compared to Highly Active SMVs with fewer lifetime mTBIs. There were no other statistically significant differences for MVAE participation, mTBI history, or their interactions. Conclusions History of one or more lifetime mTBIs was not associated with measures of brain gray matter volumes, suggesting that declines in structural brain health are not expected for the most SMVs with mTBI(s). Although MVAE may benefit brain health, a positive association between self-reported MVAE participation and gray matter volumes was not observed.